K+/H+-antiporter nigericin arrests DNA synthesis in Ehrlich ascites carcinoma cells. - Margolis, L B (1989)
Acidification of the cytoplasm of Ehrlich ascites carcinoma cells to pH 6.3 arrests DNA synthesis in these cells. Such an effect can be achieved by incubating the cells at pH 6.2 or by adding low concentrations of the K+/H+ antiporter, the antibiotic nigericin, at neutral pH. Glucose and anaerobiosis potentiate the nigericin effect. The inhibition of DNA synthesis by nigericin occurs without any significant decrease in the ATP concentration and in the mitochondrial membrane potential. The DNA synthesis inhibition is caused neither by a decrease in the intracellular [K+] nor by an increase in the intracellular [Na+] accompanying the nigericin effect (at least at low concentrations of the antibiotic). Nigericin should thus be regarded as a type of a cytostatic primarily affecting intracellular pH.